Characterization of Acidic Soils in the Highlands of Tsegede, Tigray, Ethiopia - Hadera, Abreha Kidanemariam (Soil Acidity Characterization and Effects of Liming and Chemical Fertilization on Microbial Growth, Nutrient Uptake and Yield of Wheat (Triticum aestivum L.): The Case of Acidic Soils in Tsegede District, Northern Ethiopia, Edition 1, 2024)
This study intended to characterize the physico-chemical and mineralogical properties of acidic soils under three land use types in the Tsegede highlands, in the Tigray region of Ethiopia. Soil samples were collected from three sites and under three land-use types namely cultivated, grazing and forest land soils. Analytical results of the soil taken from 0-30 cm depth revealed that silt content, exchangeable Al and Al saturation percentage were significantly affected (P \(\le\) 0.05) by site, land use and their interaction whereas pH, organic matter (OM) and total N were significantly (P \(\le\) 0.05) influenced by site and land use type. Likewise, sand content, available P, exchangeable acidity, exchangeable Na, K, Ca, Mg and CEC were significantly (P \(\le\) 0.05) affected only by land use while bulk density (P \(\le\) 0.05) by site. However, distributions of sand and clay were affected by both land use and depth at the 0-90 cm depth whereas OM content was varied only across depth. At the 0-30 cm depth layer, soil pH values were 4.87, 5.06 and 5.47 in the grazing, cultivated and forest land soils, respectively, and its average (5.08) showed a negative correlation with exchangeable acidity (r = -0.77**) and Al (r = -0.86**). At the 0-30 cm depth, the overall soil OM accumulation (8.87%) was high while available P status was low (10.60 mg kg-1) revealing a positive correlation with pH (r = 0.65**) and negative correlations with exchangeable acidity (r = -0.58*) and Al (r = -0.53*). Quartz, tridymite, limonite, nacrite, kaolinite, muscovite, vermiculite and labradorite clay minerals were identified. About 50% of the area falls under very strongly acidic soil with more of its coverage in the grazing and lower in the forest land soils. Intensive weathering of soil parent materials by excessive leaching and desilication aggravated by crop and forage removal of basic cations are the causes of soil acidity. Hence, it is suggested that besides scaling up liming, the introduction of optimum grazing and agro-forestry practices may improve the productivity of acidic soils of the Tsegede highlands on a sustainable basis.